Argonaute proteins regulate microRNA stability: increased microRNA abundance by Argonaute proteins is due to microRNA stabilization - Winter, Julia; Diederichs, Sven (RNA biology, 2011)
Argonaute proteins are key players in microRNA (miRNA) processing and function. Next to their role as RISC effector proteins mediating target silencing, they actively participate in miRNA biogenesis and increase miRNA abundance by a yet unidentified mechanism. It has been hypothesized that this increase in steady-state miRNA levels might be due to a stabilizing effect of Argonaute proteins, but this has not been analyzed so far due to a lack of test systems. Here, we provide two approaches to estimate miRNA stability and factors affecting it: in cells lacking Ago2, endogenous miRNA guide strand degradation and half-lives can be assessed using Actinomycin D or α-Amanitin. In turn, miRNA passenger strands can serve as a model in wildtype cells to ascertain the impact of miRNA stability factors.We provide evidence that Argonaute proteins stabilize mature miRNAs in a slicing-independent manner. Transcriptional inhibition reveals reduced half-lives of multiple endogenous miRNA guide strands in cells lacking Ago2. This effect is reversible upon the reconstitution of Argonaute expression. Correspondingly, overexpression of Argonaute proteins decelerates miRNA degradation and increases miRNA half-life. Taken together, this study employs two model systems to identify factors altering miRNA stability and provides evidence how Argonaute proteins post-transcriptionally elevate mature miRNA levels via increasing miRNA stability.
Gesehen am 07.11.2022